AN ANALYSIS OF DIRECTIVE SPEECH ACT IN “PUSS IN BOOTS : THE LAST WISH” MOVIE - Syahcorina, Oscar Dela; Delfi, Syofia; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to find out the types of Directive Speech Acts bythe main characters “Puss in "Puss in Boots: The Last Wish" movie and analyze thetypes of directive speech act that most dominant used in the movie. The research utilized a qualitative descriptive research approach to qualitatively collect and interpret data for analyzing speech acts, employing the documentation technique for data collection and thematic analysis for data analysis. The object of this research is Puss in Boots: The Last Wish directed by Joel Crawford. From the result of this research, theresearcher finds that there are 55 utterances of directive speech act used by Puss. Theresult show that, first, the types of directives speech act were Command, Order,Request, and Suggestion. Second, the types of directive speech act that most dominantused were command type. In term of types, command is the most dominant used (25utterances) and order (6 utterances) is the rarely used type. Through examining specificscenes, the research reveals how Puss employs these speech acts to influence others and advance the plot. This research also highlights the strategic use of different directivetypes to achieve specific communicative goals, showcasing the nuanced role oflanguage in animated storytelling.Key Words: Speech act, Directive Speech Act, A movie